Analysis of Market Orientation, Innovation and Operational Efficiency Towards SMEs Performance at Martabak SMEs in Sukabumi City - Dian Fitriani; R. Deni Muhammad Danial; Kokom Komariah (Dinasti Publisher, 2025)
This study is motivated by the low performance of martabak micro, small and medium enterprises (MSMEs) in Sukabumi City which is allegedly caused by weak market orientation, lack of appropriate innovation, and low operational efficiency. This study aims to analyze the influence of market orientation, innovation, and operational efficiency on business performance. This research uses a quantitative approach with a causal descriptive method. The entire population of 149 businesses was sampled using saturated sampling technique. Data were collected through questionnaires and analyzed using multiple linear regression, after testing validity, reliability, and classical assumption test. Data processing used SPSS V.25 software application. The result showed that market orientation and operational efficiency had a positive and significant effect on business performance, while innovation had a negative and significant negative effect. This finding indicates that business actors have not been able to implement relevant and targeted innovation according to market needs. Therefore, it is necessary to increase understanding of the market, optimize efficiency in operational processes, and design more contextual innovative strategies so that business performance increases and business competitiveness is maintained in a sustainable manner.